1% Tirbanibulin Ointment for the Treatment of Actinic Keratoses. Issue 4 (April 2022) - Dao, Diem-Phuong D.; Sahni, Vikram Nath; Sahni, Dev Ram; Balogh, Esther A.; Grada, Ayman; Feldman, Steven R.
Objective: Actinic keratoses (AKs) are cutaneous lesions that arise in sun-damaged skin. AKs may transform into squamous cell carcinoma in situ. Tirbanibulin 1% ointment is a new topical treatment for AKs, recently approved by the Food and Drug Administration. Data Sources: The PubMed database was searched for articles published from 1960 to March 31, 2021, using the keywords tirbanibulin and Klisyri . Data Extraction: Phase 2 and phase 3 clinical trials were reviewed. Data Synthesis: In phase 2 clinical trials, 43% of patients treated with tirbanibulin experienced complete clearance by day 57 (43% [95% CI = 32, 54]). Across two phase 3 clinical trials (pooled data), complete (100%) clearance occurred in 49% of patients in tirbanibulin groups and in only 9% of the vehicle groups (difference, 41% points; 95% CI = 35 to 47; P < 0.001). Although no comparative studies are available, tirbanibulin is applied for a shorter duration (5 days) compared with diclofenac 3% gel, fluorouracil 5% cream, and imiquimod 3.75% cream. Adverse events were mild and included pruritus, application site pain, and local skin reactions. Systemic adverse events such as necrosis and angioedema, observed with other AK treatments such as fluorouracil and imiquimod, were not observed with tirbanibulin, thus giving tirbanibulin a favorable safety profile. Relevance to Patient Care and Clinical Practice: Tirbanibulin effectively reduces AK burden and recurrence and has a favorable safety profile with mild adverse events. In comparison, imiquimod, 5-flourouracil, and diclofenac can result in necrosis, angioedema, and arthralgias. Conclusion: With a favorable safety profile and short regimen, tirbanibulin is an efficacious treatment for clinicians to utilize in their treatment toolbox when treating AKs on the face and scalp.